Migration Strategies: A Comparative Analysis of South American Countries (Journal of the Spanish Institute for Strategic Studies, 2025)
Migration strategies have gained prominence on the security agendas of many countries, both in Europe and South America. The issue is particularly relevant due to the increasing presence of South-South migration, primarily driven by the economic and political crisis in Venezuela. These new migration flows have transformed traditional countries of origin into transit or destination countries. This study aims to examine and compare strategic documents from four South American countries (Colombia, Chile, Ecuador, and Perú) as well as two European countries (Portugal and Spain) as reference points. Qualitative content analysis methodology is used, and current trends and challenges are analysed. The results indicate the level of preparedness of these countries for a migration crisis, highlighting both similarities and differences in their documents.
Keywords: Strategies; migration; South America; Qualitative content analysis